CD19+CD24hiCD38hi regulatory B cells deficiency revealed severity and poor prognosis in patients with sepsis - Chunmei Wang; Huihui Xu; Rui Gao; Fengying Leng; Fangjie Huo; Yinzhen Li; Siting Liu; Mingzheng Xu; Jianwen Bai (BMC Immunology, 2022)
Abstract Background Sepsis still remains a major challenge in intensive care medicine with unacceptably high mortality among patients with septic shock. Due to current limitations of human CD19+CD24hiCD38hi Breg cells (Bregs) studies among sepsis, here, we tried to evaluate Bregs in severity and prognostic value in patients with sepsis. Methods Peripheral blood from 58 patients with sepsis and 22 healthy controls was analyzed using flow cytometry to evaluate the frequency and number of Bregs. All cases were divided into non-survived or survived group after 28 days followed up. Spearman's correlation analysis was performed on Bregs frequency and clinical indices. The area under the curve was acquired using the receiver operating characteristic analysis to assess the sensitivity and specificity of Bregs for outcome of sepsis. Survival curve analysis and binary logistic regression were applied to estimate the value of Bregs in prognosis among cases with sepsis. Results Sepsis patients had decreased proportions and number of Bregs. Sepsis patients with low frequency of Bregs were associated with an increased risk of septic shock. Bregs frequency is inversely associated with lactate, SOFA, and APACHE II and positively correlated with Tregs frequency. Low levels of Bregs closely correlated with septic outcomes. Numbers of Bregs were prediction factors for poor prognosis. Conclusions Frequency and number of Bregs decreased, and Bregs deficiency revealed poor prognosis in patients with sepsis.